Role of the Metal Surface on the Room Temperature Activation of the Alcohol and Amino Groups of p-Aminophenol - Del Árbol, Nerea Ruiz (2020)
We present a comparative study of the room-temperature adsorption of p-aminophenol (p-AP) molecules on three metal surfaces, namely Cu(110), Cu(111), and Pt(111). We show that the chemical nature and the structural symmetry of the substrate control the activation of the terminal molecular groups, which result in different arrangements of the interfacial molecular layer. To this aim, we have used in situ STM images combined with synchrotron radiation high-resolution XPS and NEXAFS spectra, and the results were simulated by DFT calculations. On copper, the interaction between the molecules and the surface is weaker on the (111) surface crystal plane than on the (110) one, favoring molecular diffusion and leading to larger ordered domains. We demonstrate that the p-AP molecule undergoes spontaneous dehydrogenation of the alcohol group to form phenoxy species on all the studied surfaces; however, this process is not complete on the less reactive surface, Cu(111). The Pt(111) surface exhibits stronger molecule-surface interaction, inducing a short-range ordered molecular arrangement that increases over time. In addition, on the highly reactive Pt(111) surface other chemical processes are evidenced, such as the dehydrogenation of the amine group.